The Radical American Judaism of Mordecai M. Kaplan - Scult, Mel (Book collections on Project MUSE., 2014)
Mordecai M. Kaplan, founder of the Jewish Reconstructionist movement, is the only rabbi to have been excommunicated by the Orthodox rabbinical establishment in America. Kaplan was indeed a heretic, rejecting such fundamental Jewish beliefs as the concept of the chosen people and a supernatural God. Although he valued the Jewish community and was a committed Zionist, his primary concern was the spiritual fulfillment of the individual. Drawing on Kaplan's 27-volume diary, Mel Scult describes the development of Kaplan's radical theology in dialogue with the thinkers and writers who mattered to.